Exploring Whether Talking With Parents, Siblings, and Friends Moderates the Association Between Peer Victimization and Adverse Psychosocial Outcomes - Hong, Jun Sung (Journal of interpersonal violence, 2021)
The purpose of this study is to explore whether talking with parents, siblings, and friends will moderate the association between peer victimization and adverse outcomes (internalizing problems, alcohol/tobacco use, and delinquent friend affiliation). Data were derived from the Health Behavior in School-Aged Children, 2009 to 2010 cohort study in the United States (n = 12,642). Bivariate, logistic regression and ordinal least squares regression analyses were conducted. Peer victimization was found to be associated with all the adverse outcomes. Although ease of talking with parents had a lower likelihood of alcohol/tobacco use, it increased alcohol/tobacco risk when peer victimization increased. Ease of talking with friends showed a higher likelihood of alcohol/tobacco use, but the likelihood was lower when peer victimization increased. Ease of talking with parents and ease of talking with friends both lowered the likelihood of delinquent friend affiliation; however, ease of talking with parents increased the risk of delinquent friend affiliation when peer victimization increased. Moreover, ease of talking with friends decreased the risk of internalizing problems, although it increased the risk of such behaviors when peer victimization increased. Talking with siblings did not buffer the association between peer victimization and adverse outcomes. Implications for practice are also discussed.